Trunk Impairment as a Predictor of Activities of Daily Living in Acute Stroke - Ishiwatari, Masahiro; Honaga, Kaoru; Tanuma, Akira; Takakura, Tomokazu; Hatori, Kozo; Kurosu, Akihiro; Fujiwara, Toshiyuki (Frontiers in Neurology, 2021)
Background and purpose: Trunk function plays a key role in performing activities of daily living (ADL) including locomotion and sitting. Sitting and ADL should be performed as early as possible especially during the acute phase of stroke rehabilitation. Therefore, this study aimed to assess trunk function among patients with acute stroke using the trunk impairment scale (TIS) and predict its functional outcomes. Methods: A total of 67 patients with acute stroke (within 48 h of stroke onset) participated in this study. The following clinical assessment items were obtained within 48 h of stroke onset and on the day before discharge from the hospital. Trunk function was examined using TIS and trunk control test (TCT). Motor function of the upper and lower extremities was assessed with stroke impairment assessment set motor score (SIAS-M), and ADL was assessed with functional independence measure motor items (FIM-M). Results: Multiple regression analysis was performed using the stepwise regression method, with total FIM-M score at discharge as the dependent variable and age, TIS, TCT, SIAS-M, and FIM-M within 48 h of stroke onset as independent variables. Age, TIS, and FIM-M within 48 h of stroke onset were selected as input variables and showed a high-adjusted determination coefficient (R2 = 0.79; P < 0.001). Conclusion: TIS is a reliable method for evaluating trunk control function and is an early predictor of ADL among patients with acute stroke.